2012
DOI: 10.5455/vetworld.2012.352-355
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial drug susceptibility of Staphylococcus aureus from subclinical bovine mastitis in Coimbatore, Tamilnadu, South India

Abstract: Aim : The study was carried out to investigate the prevalence and antimicrobial susceptibility of clinical pathogens isolated from Bovine Mastitis in and around Coimbatore District, Tamilnadu, South India. Materials and Methods: A total of 250 milk samples were screened and 152 isolates of Staphylococci were obtained and their susceptibility to several antimicrobial agents by agar disc diffusion method. Results: Out of 152 isolates of Staphylococcus aureus resistance was detected in 63 (41.44%), 39 (25.65%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 2 publications
3
23
0
1
Order By: Relevance
“…Highest sensitivity of Staphylococcus aureus isolates to Gentamicin and Ampicillin was reported by Mubarack et al, (2012) and Pavulraj et al, (2013). Resistance to cefoperazone antibiotic is unusual as this antibiotic is recently introduced in Veterinary medicine in this area.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Highest sensitivity of Staphylococcus aureus isolates to Gentamicin and Ampicillin was reported by Mubarack et al, (2012) and Pavulraj et al, (2013). Resistance to cefoperazone antibiotic is unusual as this antibiotic is recently introduced in Veterinary medicine in this area.…”
Section: Resultsmentioning
confidence: 88%
“…This organism is capable of causing peracute, acute, chronic, gangreneous and subclinical mastitis. (Miller et al, 1993;Mubarack et al, 2012;Nthawat et al, 2013;Patel et al, 2000;Pavulraj et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Natural products of higher plants may possess a new source of antimicrobial agents with possibly novel mechanisms of action [9]. Medicinal plants are rich in a wide variety of secondary metabolites such as tannins, alkaloids and flavonoids, which have been found in vitro to have antimicrobial properties [10,11]. A number of phyotherapy manuals mentioned that the various natural plants able to treat infectious diseases, fewer side effects and low toxicity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Different researchers reported antimicrobial resistant S. (Khakpoor et al, 2011) in other study reported that all isolate of S. aureus from mastitis cattle were resistant to penicillin and 83.3% resistance to ampicillin in this study is much higher than that of 41.44% as reported by (Mubarack et al ., 2012) and lower as compared to 100% resistance reported by (Khakpoor et al, 2011).The current study was highly susceptible to some antibiotics like, gentamicin (100%), streptomycin (81.8%), norfloxacin (63.6%), chloramphenicol (81.8%), sulfamethoxazole (96%), kanamycin (72.7%), polymixin B (72.7%), erythromycin (72.7%) and tetracycline (81.8); similar results were found for chloramphenicol, streptomycin and gentamycin (100, 94, and 90%), respectively by Beyene (2016) in Ethiopia but disagree with the observation made by Kassaify et al (2013) in the case of streptomycin (95%), but it disagree with the observation made by Tariku et al (2011) in the case of tetracycline (0%) and clindamycin (4%) in dairy farms in Jimma town, cefoxitin (100%) and clindamycin (each 100%) (Wang et al, 2014) in China. The probable explanation could be that S. aureus strains have the capacity to change their resistance behavior to the exposed antimicrobials.…”
Section: Discussionmentioning
confidence: 44%